Denitration and dioxin removal core-shell structure catalyst and preparation method thereof

Through the design and preparation method of core-shell structure catalyst, the problem of poor activity and susceptible sulfur poisoning under low temperature conditions is solved, and efficient dioxin degradation and flue gas purification effects are achieved. It is suitable for waste incineration and steel sintering and other fields.

CN120460014APending Publication Date: 2025-08-12DATANG NANJING ENVIRONMENTAL PROTECTION TECH

Patent Information

Application Number
CN202510548324.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The existing SCR denitrification catalysts have poor activity under low temperature conditions, are susceptible to sulfur poisoning and have low dioxin degradation efficiency, which cannot meet the actual needs of industrial flue gas purification.

Method used

The core-shell structure catalyst is used, the core layer is CeMoLaSnOx microspheres, the shell layer is porous SiO2-TiO2@ZSM-5 composite support, and the additive layer is Fe-Co-Ni-Y oxide. The core layer is prepared by ultrasonic-hydrothermal method, and the shell layer is covered by sol-gel method, and the structure and performance of the catalyst are optimized through calcination treatment at different stages.

Benefits of technology

It improves the low-temperature activity of the catalyst, anti-sulfur poisoning performance and dioxin degradation efficiency, enhances the adsorption and catalytic conversion capabilities of complex pollutants, and is suitable for the coordinated purification of low-temperature flue gases such as waste incineration and steel sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005381347170000111
    Figure BDA0005381347170000111
  • Figure BDA0005381347170000121
    Figure BDA0005381347170000121
  • Figure BDA0005381347170000131
    Figure BDA0005381347170000131
Patent Text Reader

Abstract

The invention relates to the technical field of SCR denitration catalyst preparation, in particular to a denitration and dioxin removal core-shell structure catalyst and a preparation method thereof.The denitration and dioxin removal core-shell structure catalyst comprises 50-65 wt% of a core layer, 25-35 wt% of a shell layer and 5-15 wt% of an auxiliary layer, and the core layer is CeMoLaSnOx microspheres; the shell layer is a porous SiO2-TiO2 (at) ZSM-5 composite carrier; and the auxiliary agent layer is a Fe-Co-Ni-Y oxide. The prepared denitration and dioxin removal core-shell structure catalyst has good sulfur resistance and water poisoning resistance, effectively overcomes the defects that a traditional denitration catalyst is poor in low-temperature activity, prone to sulfur poisoning, low in dioxin degradation efficiency and the like, and can be widely applied to collaborative purification of low-temperature flue gas generated in waste incineration, steel sintering and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of SCR denitration catalyst preparation, in particular to a denitration and dedioxin core-shell structure catalyst and a preparation method thereof. Background Art

[0002] Nitrogen oxides (NO x ) and dioxins (PCDD / Fs) are major pollutants that endanger the environment and human health, mainly from industries such as thermal power generation, steel smelting, and waste incineration. Currently, commercial V2O5-WO3 / TiO2 catalysts have high denitrification efficiency in the temperature range of 300-400℃, but still have significant drawbacks:

[0003] Insufficient low-temperature activity: When the flue gas temperature is below 300°C, the denitrification efficiency of the catalyst decreases significantly, making it difficult to meet the requirements of low-temperature working conditions;

[0004] Sulfur poisoning: SO2 in industrial flue gas will react with the catalyst, covering or destroying the active center, reducing catalytic activity and service life;

[0005] Low dioxin degradation efficiency: Traditional catalysts have limited catalytic degradation capabilities for dioxins, making it difficult to achieve efficient synergistic removal.

[0006] In response to the above problems, existing patented technologies have proposed some improvement solutions, but they still have limitations:

[0007] The invention patent CN116747874B uses a Ce-Co bimetallic framework catalyst, which improves low-temperature activity and dioxin degradation performance, but lacks stability and sulfur resistance;

[0008] The invention patent CN119368165A widens the temperature window by coating with SiO2, but the preparation process is complicated and the degradation effect on dioxins is limited;

[0009] The invention patent CN114433083B introduces rare earth metal praseodymium and precious metals into V2O5 / WO3 / TiO2, which reduces the denitrification temperature and inhibits dioxin emissions, but the cost is high and its industrial application is limited.

[0010] In summary, existing catalysts still cannot meet the requirements of low-temperature, high-efficiency denitrification, sulfur poisoning resistance, highly selective dioxin degradation, simple preparation, and long-term stability. Therefore, there is an urgent need to develop a new type of synergistic denitrification and dioxin removal catalyst that is efficient, stable, and simple to process to meet the actual needs of industrial flue gas purification. Summary of the Invention

[0011] The purpose of the present invention is to provide a denitration and dioxin removal core-shell structure catalyst and its preparation method to solve the problems of poor low-temperature activity, easy sulfur poisoning and low dioxin degradation efficiency of traditional denitration catalysts.

[0012] In the first aspect, the present invention provides a denitration and dioxin removal core-shell structure catalyst, which comprises a core layer of 50-65wt%, a shell layer of 25-35wt% and an auxiliary agent layer of 5-15wt%.

[0013] The core layer is CeMoLaSnO x microspheres;

[0014] The shell layer is a porous SiO2-TiO2@ZSM-5 composite support;

[0015] The auxiliary agent layer is Fe-Co-Ni-Y oxide.

[0016] The core layer of the denitration and dioxin removal core-shell structure catalyst of the present invention is CeMoLaSnO x The microspheres, the shell layer is a porous SiO2-TiO2@ZSM-5 composite support, the additive layer is Fe-Co-Ni-Y oxide, among which the core layer is CeMoLaSnO x The microspheres have uniform particle size and a mesoporous structure on the surface, which greatly increases the active sites of the catalyst and improves the dioxin degradation efficiency. x The synergistic effect of the Ce-Mo-La-Sn composite oxide in the microspheres further enhances the oxygen vacancy concentration and thermal stability, improving the catalyst's adsorption and catalytic conversion capabilities for complex pollutants, and effectively improving the removal efficiency of dioxins and nitrogen oxides. The shell SiO2-TiO2@ZSM-5 composite support has a specific specific surface area and pore size range, which can effectively wrap the core layer and protect the active ingredients in the core layer. The acidic sites and shape-selective catalytic properties of the SiO2-TiO2@ZSM-5 composite support itself cooperate with the core layer to further enhance the adsorption and conversion capabilities of the reactants, enhancing the overall activity and selectivity of the catalyst. Finally, the Fe-Co-Ni-Y composite oxide is used as the additive layer. The combined action of the different metal elements of Fe-Co-Ni-Y further enhances the catalyst's electron transfer capacity and redox activity. Therefore, the denitrification and de-dioxination core-shell structure catalyst prepared by the present invention has good resistance to sulfur and water poisoning, effectively compensating for the shortcomings of traditional denitrification catalysts, such as poor low-temperature activity, susceptibility to sulfur poisoning, and low dioxin degradation efficiency.

[0017] As a preferred technical solution, the CeMoLaSnO xIn the microspheres, the molar ratio of Ce, Mo, La and Sn is 1: (0.1-1): (0.1-0.5): (0.05-0.3), and the CeMoLaSnO x The particle size of the microspheres is 1 to 3 μm, and the surface has a mesoporous structure with a pore size of 2 to 8 nm.

[0018] As a preferred embodiment of this technical solution, the specific surface area of the porous SiO2-TiO2@ZSM-5 composite carrier is 300-650m 2 / g, pore size is 5-12nm.

[0019] As a preferred embodiment of the present technical solution, in the Fe-Co-Ni-Y oxide, the molar ratio of Fe, Co, Ni and Y is 1:(1-3):(0.1-1):(0.05-0.3).

[0020] In a second aspect, the present invention further provides a method for preparing the above-mentioned denitration and dedioxination core-shell structure catalyst, which specifically comprises the following steps:

[0021] S1, cerium nitrate, ammonium molybdate, lanthanum nitrate, and tin tetrachloride were dissolved in a glycol-water mixed solvent in proportion, citric acid was added, and hydrothermal reaction was carried out under ultrasonic conditions, followed by washing, drying, and calcination to obtain CeMoLaSnO x microspheres;

[0022] S2, disperse ZSM-5 molecular sieve in ethanol solution of tetrabutyl titanate and ethyl silicate, add acetic acid to adjust the pH to 4-6, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined to obtain SiO2-TiO2@ZSM-5 coated core-shell materials;

[0023] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and iridium nitrate in deionized water in proportion, add a silane coupling agent, impregnate the core-shell material, dry and calcine to obtain a denitration and dedioxin core-shell structure catalyst.

[0024] In the present invention, CeMoLaSnO x In the preparation method of microspheres, first, the metal ions (Ce 3+ 、Mo 6+ 、La 3+ 、Sn 4+) is evenly dispersed to avoid agglomeration, while promoting the chelation of citric acid and metal ions to form a uniform precursor complex; the precursor complex undergoes hydrolysis and condensation reactions in an ethylene glycol-water mixed solvent under high temperature and high pressure to form primary microspheres of Ce-Mo-La-Sn composite oxide, and the mechanical vibration of ultrasound can further refine the particle size and induce the formation of a mesoporous structure; citric acid, as an organic template, decomposes during the calcination process to produce gases (CO2, H2O), leaving behind abundant mesoporous channels. Therefore, the ultrasound-assisted hydrothermal process optimizes the pore distribution and forms a mesoporous structure with a high specific surface area, providing conditions for reactant diffusion and active site exposure. In addition, CeMoLaSnO x In microspheres, Ce 4+ / Ce 3+ The redox cycle of Sn 4+ The doping of La increases the oxygen vacancy concentration and promotes the oxygen migration ability. 3+ The introduction of CeO2 inhibits the sintering of the CeO2 lattice, and Mo 6+ The high valence state of Ce-Mo enhances the acid sites and synergistically improves the stability of the catalyst at high temperatures, while Ce-Mo is responsible for the redox reaction and La-Sn is responsible for regulating the surface acidity and adsorption capacity, synergistically catalyzing the cracking of dioxins and NO x The core layer of the catalyst of the present invention achieves the reduction of complex pollutants (NO) by regulating the multi-scale structure (mesopores, oxygen vacancies, particle size) of the material through ultrasound-hydrothermal synergy, combined with the electronic synergistic effect of multi-metal components. x , dioxins) can be removed efficiently through synergistic removal.

[0025] In the preparation of the SiO2-TiO2@ZSM-5 coated core-shell material of the present invention, a composite carrier is formed by a sol-gel method, and a porous shell layer is used to wrap the core layer to prevent the active components from sintering and losing at high temperatures or during reactions; at the same time, the microporous structure of ZSM-5 (0.5-0.6nm) can screen reactive molecules of a specific size and improve selectivity; in addition, the ZSM-5 The synergistic effect of acid sites and the Lewis acid sites of TiO2 can further enhance the adsorption and activation ability of reactants. Finally, the SiO2-TiO2 network structure can also improve the mechanical strength and thermal stability of the catalyst. Specifically, during the preparation process, the ZSM-5 molecular sieve is pre-dispersed in the sol to ensure its uniform composite with the SiO2-TiO2 and avoid uneven distribution of active components in the shell. The pH is further adjusted to a weak acidity using acetic acid to control the hydrolysis rate of tetrabutyl titanate and ethyl silicate, forming a uniform and stable SiO2-TiO2 sol to avoid rapid gelation or phase separation. Finally, the organic template is removed through calcination, which not only forms a stable porous structure, but also enhances the bonding strength between the shell and the core layer.

[0026] Finally, Fe-Co-Ni-Y composite oxide is introduced into the additive layer. The composite effect of different metal elements Fe-Co-Ni-Y can significantly increase the electron transfer ability and redox activity of the catalyst, improve the low-temperature denitrification and dedioxin performance of the catalyst, reduce the SO2 oxidation rate, and effectively inhibit the corrosion of sulfur substances on active components.

[0027] As a preferred embodiment of the present technical solution, in step S1, the volume ratio of ethylene glycol to water in the ethylene glycol-water mixed solvent is 1:(2-4);

[0028] The molar ratio of the citric acid to the total metal amount is 1.2:1.

[0029] As a preferred embodiment of the present invention, in step S1, the power of the ultrasonic wave is 200-300w,

[0030] During the hydrothermal reaction, the temperature is controlled to be 160-200° C. and the time is 12-24 hours.

[0031] As a preferred embodiment of the present technical solution, in step S2, the mass ratio of SiO2, TiO2 and ZSM-5 is 1:(0.1-1):(0.1-0.5).

[0032] As a preferred embodiment of the present technical solution, in step S3, the silane coupling agent is 3-aminopropyltriethoxysilane, and the added amount of the silane coupling agent is 5% to 10% of the total mass of the Fe-Co-Ni-Y oxide.

[0033] As a preferred embodiment of the present invention, in step S1, during the calcination, the temperature is controlled to be 450-600°C and the time is 3-5h;

[0034] In step S2, during the calcination, the temperature is controlled to be 450-550° C. and the time is 1-3 hours;

[0035] In step S3, during the calcination, the temperature is controlled to be 350-550° C. and the time is 2-4 hours.

[0036] The present invention selects different temperature treatments during the continuous calcination treatment stage, which can effectively regulate the thermodynamic behavior and kinetic process of the material, achieve the precise construction of the core-shell structure, optimize the interfacial active sites and enhance the long-term stability.

[0037] Specifically, the electronic structure of the catalyst is optimized by regulating the lattice mismatch at the core-shell interface; the metal diffusion rate is regulated to avoid structural collapse caused by excessive migration, while promoting the formation of active sites; the reduction of the metal precursor and the stable formation of the oxide shell are achieved to ensure atomic-level dispersion of the core-shell interface; the surface adsorption capacity of the catalyst is regulated, while suppressing the negative impact of the ligand effect on the catalytic activity.

[0038] The core-shell structure catalyst for denitration and dioxin removal of the present invention has at least the following beneficial effects:

[0039] 1. The present invention prepares the core layer CeMoLaSnO by a specific hydrothermal reaction and ultrasound-assisted means. x Microspheres, CeMoLaSnO x The microspheres have a uniform particle size and a mesoporous surface structure, which significantly increases the catalyst's active sites, facilitating denitrification and dioxin removal. Furthermore, the synergistic effect of the Ce-Mo-La-Sn composite oxide in the core layer further enhances oxygen vacancy concentration and thermal stability, improving the catalyst's ability to adsorb and catalytically convert complex pollutants, effectively increasing the removal efficiency of dioxins and nitrogen oxides.

[0040] 2. The shell layer of the present invention adopts a porous SiO2-TiO2@ZSM-5 composite carrier, which has a specific specific surface area and pore size range, and can effectively wrap the core layer and protect the active ingredients of the core layer. In addition, the acidic sites and shape-selective catalytic properties of the SiO2-TiO2@ZSM-5 composite carrier itself cooperate with the core layer to further improve the adsorption and conversion capacity of the reaction molecules, thereby enhancing the overall activity and selectivity of the catalyst.

[0041] 3. The present invention introduces Fe-Co-Ni-Y composite oxide into the additive layer. The composite effect of different metal elements Fe-Co-Ni-Y increases the electron transfer ability and redox activity of the catalyst. Among them, Fe provides abundant adsorption sites, Co / Ni optimizes electron transfer, and Y has a sulfur-fixing effect, which improves the low-temperature denitrification and dioxin removal performance of the catalyst, significantly reduces the SO2 oxidation rate, and effectively inhibits the corrosion of sulfur substances on the active components.

[0042] 4. The present invention uses an ultrasound-assisted hydrothermal method to synthesize core-layer microspheres, combined with sol-gel coating and aminosilane coupling agent directional loading additives, to achieve high dispersion of components and strong interface bonding through self-assembly. At the same time, by controlling the calcination temperature gradient at different stages, the crystal structure and pore stability are further optimized, ensuring that the catalyst maintains excellent mechanical strength and reactivity.

[0043] 5. The denitrification and dedioxination core-shell structure catalyst prepared by the present invention has good resistance to sulfur and water poisoning, effectively making up for the defects of traditional denitrification catalysts such as poor low-temperature activity, easy sulfur poisoning, and low dioxin degradation efficiency. It can be widely used in the coordinated purification of low-temperature flue gases such as waste incineration and steel sintering. DETAILED DESCRIPTION

[0044] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present application belongs.

[0045] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular also includes the plural. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.

[0046] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0047] Example 1

[0048] Composition of denitrification and dedioxin core-shell structure catalyst:

[0049] Core layer: CeMoLaSnO x The microspheres account for 58%, and the molar ratio of Ce, Mo, La, and Sn is 1:0.5:0.3:0.2;

[0050] Shell: SiO2-TiO2@ZSM-5 composite carrier accounts for 27.5%, with a specific surface area of 532m 2 / g, pore size 5.6nm, mass ratio of SiO2, TiO2, ZSM-5 = 1:0.6:0.4;

[0051] Auxiliary agent layer: Fe-Co-Ni-Y oxide accounts for 14.5%, and the molar ratio of Fe, Co, Ni and Y is 1:2:0.5:0.2.

[0052] Preparation method of denitrification and dioxin removal core-shell structure catalyst:

[0053] S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate and tin tetrachloride in a mixture of ethylene glycol and water at a volume ratio of 1:3.5, add citric acid, and hydrothermally react at 180°C with an ultrasonic power of 250W for 18 hours. After washing and drying, calcinate at 550°C for 4 hours to obtain CeMoLaSnO x microspheres, particle size 1.8 μm, pore size 3.5 nm;

[0054] S2, disperse ZSM-5 in tetrabutyl titanate / ethyl silicate ethanol solution, add acetic acid to adjust the pH to 5, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined at 530 °C for 2 h to obtain SiO2-TiO2@ZSM-5 coated core-shell materials;

[0055] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and yttrium nitrate in water, add 8% 3-aminopropyltriethoxysilane, and calcine at 460° C. for 3 h to obtain the target catalyst.

[0056] Example 2

[0057] Composition of denitrification and dedioxin core-shell structure catalyst:

[0058] Core layer: CeMoLaSnO x The microspheres account for 50%, and the molar ratio of Ce, Mo, La, and Sn is 1:0.1:0.1:0.05;

[0059] Shell: SiO2-TiO2@ZSM-5 composite carrier accounts for 35%, with a specific surface area of 300m 2 / g, pore size 5nm, mass ratio of SiO2, TiO2, ZSM-5 = 1:0.1:0.1;

[0060] Auxiliary agent layer: Fe-Co-Ni-Y oxide accounts for 15%, and the molar ratio of Fe, Co, Ni, and Y is 1:1:0.1:0.05.

[0061] Preparation method of denitrification and dioxin removal core-shell structure catalyst:

[0062] S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate and tin tetrachloride in a mixture of ethylene glycol and water at a volume ratio of 1:2, add citric acid, and hydrothermally react at 160°C with an ultrasonic power of 200W for 12 hours. After washing and drying, calcinate at 450°C for 4 hours to obtain CeMoLaSnO x microspheres, particle size 1.2 μm, pore size 2 nm;

[0063] S2, disperse ZSM-5 in tetrabutyl titanate / ethyl silicate ethanol solution, add acetic acid to adjust the pH to 4, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined at 450 °C for 2 h to obtain SiO2-TiO2@ZSM-5 coated core-shell materials;

[0064] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and yttrium nitrate in water, add 5% 3-aminopropyltriethoxysilane, and calcine at 350° C. for 3 h to obtain the target catalyst.

[0065] Example 3

[0066] Composition of denitrification and dedioxin core-shell structure catalyst:

[0067] Core layer: CeMoLaSnO x The microspheres account for 65%, and the molar ratio of Ce, Mo, La, and Sn is 1:1:0.5:0.3;

[0068] Shell: SiO2-TiO2@ZSM-5 composite carrier accounts for 25%, with a specific surface area of 650m 2 / g, pore size 12nm, mass ratio of SiO2, TiO2, ZSM-5 = 1:1:0.5;

[0069] Auxiliary agent layer: Fe-Co-Ni-Y oxide accounts for 10%, and the molar ratio of Fe, Co, Ni, and Y is 1:3:1:0.3.

[0070] Preparation method of denitrification and dioxin removal core-shell structure catalyst:

[0071] S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate and tin tetrachloride in a mixture of ethylene glycol and water at a volume ratio of 1:4, add citric acid, and hydrothermally react at 200°C and 300W ultrasonic power for 24 hours. After washing and drying, calcinate at 600°C for 4 hours to obtain CeMoLaSnO x microspheres, particle size 3 μm, pore size 8 nm;

[0072] S2, disperse ZSM-5 in tetrabutyl titanate / ethyl silicate ethanol solution, add acetic acid to adjust the pH to 6, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined at 550 °C for 2 h to obtain SiO2-TiO2@ZSM-5 coated core-shell materials;

[0073] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and yttrium nitrate in water, add 10% 3-aminopropyltriethoxysilane, and calcine at 550° C. for 3 h to obtain the target catalyst.

[0074] Example 4

[0075] Composition of denitrification and dedioxin core-shell structure catalyst:

[0076] Core layer: CeMoLaSnO x The microspheres account for 51%, and the molar ratio of Ce, Mo, La, and Sn is 1:0.3:0.3:0.25;

[0077] Shell: SiO2-TiO2@ZSM-5 composite carrier accounts for 34%, with a specific surface area of 423m 2 / g, pore size 10.6nm, mass ratio of SiO2, TiO2, ZSM-5 = 1:0.3:0.35;

[0078] Auxiliary agent layer: Fe-Co-Ni-Y oxide accounts for 15%, and the molar ratio of Fe:Co:Ni:Y is 1:1.8:0.65:0.18.

[0079] Preparation method of denitrification and dioxin removal core-shell structure catalyst:

[0080] S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate and tin tetrachloride in ethylene glycol-water mixture at a volume ratio of 1:2.8, add citric acid, and hydrothermally react at 185°C and ultrasonic power of 230W for 17 hours. After washing and drying, calcinate at 560°C for 4 hours to obtain CeMoLaSnO x microspheres, particle size 1.9 μm, pore size 3.6 nm;

[0081] S2, disperse ZSM-5 in tetrabutyl titanate / ethyl silicate ethanol solution, add acetic acid to adjust the pH to 5.5, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined at 470 °C for 2 h to obtain SiO2-TiO2@ZSM-5 coated core-shell materials.

[0082] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and yttrium nitrate in water, add 6.5% of 3-aminopropyltriethoxysilane, and calcine at 370° C. for 3 h to obtain the target catalyst.

[0083] Example 5

[0084] Composition of denitrification and dedioxin core-shell structure catalyst:

[0085] Core layer: CeMoLaSnO x The microspheres account for 63%, and the molar ratio of Ce, Mo, La, and Sn is 1:0.8:0.3:0.1;

[0086] Shell: SiO2-TiO2@ZSM-5 composite carrier accounts for 25%, with a specific surface area of 570m 2 / g, pore size 6.9nm, mass ratio of SiO2, TiO2, ZSM-5 = 1:0.7:0.2;

[0087] Auxiliary agent layer: Fe-Co-Ni-Y oxide accounts for 12%, and the molar ratio of Fe, Co, Ni, and Y is 1:2.3:0.6:0.15.

[0088] Preparation method of denitrification and dioxin removal core-shell structure catalyst:

[0089] S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate and tin tetrachloride in a mixture of ethylene glycol and water at a volume ratio of 1:3.3, add citric acid, and hydrothermally react at 175°C with an ultrasonic power of 280W for 21.5 hours. After washing and drying, calcinate at 575°C for 4 hours to obtain CeMoLaSnO x microspheres, particle size 2.2 μm, pore size 6.9 nm;

[0090] S2, disperse ZSM-5 in tetrabutyl titanate / ethyl silicate ethanol solution, add acetic acid to adjust the pH to 4.5, form SiO2-TiO2 sol, and mix CeMoLaSnO x The microspheres were immersed in the sol, centrifuged, dried, and calcined at 515 °C for 2 h to obtain SiO2-TiO2@ZSM-5 coated core-shell materials.

[0091] S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and yttrium nitrate in water, add 8.5% of 3-aminopropyltriethoxysilane, and calcine at 410° C. for 3 h to obtain the target catalyst.

[0092] Comparative Example 1

[0093] The formula and preparation process are basically the same as those in Example 1, except that:

[0094] Core layer: CeMoLaSnO x microspheres, accounting for 85%;

[0095] Shell composition: SiO2-TiO2@ZSM-5 composite support, accounting for 13%;

[0096] Auxiliary agent layer: Fe-Co-Ni-Y oxide, accounting for 2%.

[0097] Comparative Example 2

[0098] The formula and preparation process are basically the same as those in Example 1, except that:

[0099] Shell layer: SiO2-TiO2 composite carrier, accounting for 27.5%.

[0100] Comparative Example 3

[0101] The formula and preparation process are basically the same as those in Example 1, except that:

[0102] Auxiliary agent layer: Fe-Co-Ni oxide, accounting for 14.5%.

[0103] Comparative Example 4

[0104] The formula and preparation process are basically the same as those in Example 1, except that:

[0105] The calcination temperature in step S1 is 400°C.

[0106] Test example

[0107] In order to study the activity of the catalysts prepared in the above embodiments and control examples, the denitrification efficiency and dechlorobenzene removal efficiency were tested at a flue gas temperature of 150-400°C. The test results are shown in Table 1.

[0108] The test conditions are as follows: NH3 volume concentration 500ppm, NH3 / NO=1, chlorobenzene concentration 500ppm, SO2 volume concentration 400ppm (introduced during use), H2O volume concentration 15% (introduced during use), GHSV=60000h -1 .

[0109] Table 1 Catalyst denitrification efficiency and dechlorobenzene efficiency

[0110]

[0111]

[0112]

[0113] As shown in Table 1, the denitration and dioxin removal catalyst prepared by the present invention exhibits good denitration and dechlorobenzene (de-dioxin) performance at temperatures between 150 and 400°C, and exhibits good resistance to sulfur-water poisoning. However, when the ratio of the core layer, shell layer, and additive layer is adjusted, or when different core layers and additive layers are selected, the denitration and de-chlorobenzene efficiencies of the resulting catalysts decrease to varying degrees. This further demonstrates that the performance of the denitration and de-dioxin removal core-shell catalyst of the present invention is the result of the interaction between the composition and ratio of the core layer, shell layer, and additive layer, as well as the specific preparation method.

[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A denitrification and dedioxination core-shell catalyst, characterized in that: The denitration and dioxin removal core-shell structure catalyst comprises a core layer of 50-65 wt%, a shell layer of 25-35 wt% and an auxiliary agent layer of 5-15 wt%. The core layer is CeMoLaSnOx microspheres; The shell layer is a porous SiO2-TiO2@ZSM-5 composite support; The auxiliary agent layer is Fe-Co-Ni-Y oxide.

2. The denitration and dioxin removal core-shell structure catalyst according to claim 1, characterized in that: In the CeMoLaSnOx microspheres, the molar ratio of Ce, Mo, La and Sn is 1:(0.1-1):(0.1-0.5):(0.05-0.3), and the particle size of the CeMoLaSnOx microspheres is 1-3 μm, and the surface has a mesoporous structure with a pore size of 2-8 nm.

3. The denitration and dioxin removal core-shell structure catalyst according to claim 1, characterized in that: The specific surface area of the porous SiO2-TiO2@ZSM-5 composite carrier is 300-650m 2 / g, pore size is 5-12nm.

4. The denitration and dioxin removal core-shell structure catalyst according to claim 1, characterized in that: In the Fe-Co-Ni-Y oxide, the molar ratio of Fe, Co, Ni and Y is 1:(1-3):(0.1-1):(0.05-0.3).

5. The method for preparing the denitration and dedioxination core-shell structure catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Dissolve cerium nitrate, ammonium molybdate, lanthanum nitrate, and tin tetrachloride in a proportionate amount in an ethylene glycol-water mixed solvent, add citric acid, and perform a hydrothermal reaction under ultrasonic conditions. The mixture is then washed, dried, and calcined to obtain CeMoLaSnOx microspheres. S2, dispersing ZSM-5 molecular sieve in an ethanol solution of tetrabutyl titanate and ethyl silicate, adding acetic acid to adjust the pH to 4-6 to form a SiO2-TiO2 sol, immersing CeMoLaSnOx microspheres in the sol, and obtaining a SiO2-TiO2@ZSM-5 coated core-shell material after centrifugation, drying, and calcination; S3. Dissolve ferric nitrate, cobalt nitrate, nickel nitrate and iridium nitrate in deionized water in proportion, add a silane coupling agent, impregnate the core-shell material, dry and calcine to obtain a denitration and dedioxin core-shell structure catalyst.

6. The preparation method according to claim 5, characterized in that In step S1, the volume ratio of ethylene glycol to water in the ethylene glycol-water mixed solvent is 1:(2-4); The molar ratio of the citric acid to the total metal amount is 1.2:

1.

7. The preparation method according to claim 5, characterized in that In step S1, the power of the ultrasonic wave is 200-300w. During the hydrothermal reaction, the temperature is controlled to be 160-200° C. and the time is 12-24 hours.

8. The preparation method according to claim 5, characterized in that In step S2, the mass ratio of SiO2, TiO2 and ZSM-5 is 1:(0.1-1):(0.1-0.5).

9. The preparation method according to claim 5, characterized in that In step S3, the silane coupling agent is 3-aminopropyltriethoxysilane, and the added amount of the silane coupling agent is 5% to 10% of the total mass of the Fe-Co-Ni-Y oxide.

10. The preparation method according to claim 5, characterized in that In step S1, during the calcination, the temperature is controlled to be 450-600°C and the time is 3-5 hours; In step S2, during the calcination, the temperature is controlled to be 450-550° C. and the time is 1-3 hours; In step S3, during the calcination, the temperature is controlled to be 350-550° C. and the time is 2-4 hours.

Citation Information

Patent Citations

  • Preparation method of catalysts for denitrification and dioxin degradation

    CN114433083B

  • CeWOx-coated SiO2 wide-temperature denitration catalyst as well as preparation method and application thereof

    CN119368165A

Cited By

  • Catalyst for low-temperature denitration and synergistic decomposition of dioxin and preparation method thereof

    CN121669228A

  • Denitration catalyst with low SO2 / SO3 conversion rate and preparation method thereof

    CN122124826A